Innovative Strategies in Physical Education to Encourage Children's Physical Activity in the Digital Age - Firayani, Firayani (PT. Anagata Sembagi Education, 2024)
Physical education plays an important role in forming healthy and active lifestyle habits for children. However, in the increasingly advanced digital era, children's physical activity has decreased significantly due to high exposure to technology and sedentary lifestyles. This article aims to explore innovative strategies that can be applied in physical education to increase children's motivation and participation in physical activity. This study uses a qualitative method with a case study approach in several elementary schools that have implemented innovative methods, such as gamification, the use of mobile applications, and interactive technology-based activities. The results of the study show that these innovative strategies can increase children's interest and consistency in doing physical activities, thereby helping to reduce the risk of health problems due to inactive lifestyles. The implementation of appropriate technology in physical education learning has a positive impact on developing healthy lifestyle habits while accommodating the characteristics of the digital generation. This article recommends the development of an integrated curriculum with technology and training for physical education teachers to maximize the use of innovative strategies.